Neither too much nor too little: mitochondrial calcium concentration as a balance between physiological and pathological conditions - D’Angelo, Donato; Vecellio Reane, Denis; Raffaello, Anna (Frontiers in Molecular Biosciences, 2023)
Ca 2+ ions serve as pleiotropic second messengers in the cell, regulating several cellular processes. Mitochondria play a fundamental role in Ca 2+ homeostasis since mitochondrial Ca 2+ (mitCa 2+ ) is a key regulator of oxidative metabolism and cell death. MitCa 2+ uptake is mediated by the mitochondrial Ca 2+ uniporter complex (MCUc) localized in the inner mitochondrial membrane (IMM). MitCa 2+ uptake stimulates the activity of three key enzymes of the Krebs cycle, thereby modulating ATP production and promoting oxidative metabolism.As Paracelsus stated, "Dosis sola facit venenum", in pathological conditions, mitCa 2+ overload triggers the opening of the mitochondrial permeability transition pore (mPTP), enabling the release of apoptotic factors and ultimately leading to cell death. Excessive mitCa 2+ accumulation is also associated with a pathological increase of reactive oxygen species (ROS). In this article, we review the precise regulation and the effectors of mitCa 2+ in physiopathological processes.